FABRICAÇÃO ROBÓTICA EM ARQUITECTURA - Princípios, processos e aplicações - José Carlos Gomes Campos (2016)
The increasing integration of robotic technologies in various research centres, as well as architecture practices, justifies the pertinence of this study, which seeks to develop a critical reflection about these technologies, as well as some of its processes and applications known up to this date. After an attempt to introduce robotics in construction - which occurred in Japan during the late 80's and 90's - the exploration of this technology took a new breath after 2005, revived by architects who found in the industrial robotic arm a potential ally to materialize their most elaborate ideas. Since that period, investigations related to robotics applied to architecture have increased, which lead to the realization of several innovative projects. The objective of this work will focus mainly on study of assimilation and use of the robotic arm in architecture, identifying the historical background of this technology, as well as its fundamental principles and processes. Furthermore, it is also intended to reflect on the ways in which this tool is being accepted in the fields of architecture and construction, shaping professional relations in the world of construction. For this study, this dissertation uses a selection of case studies organized per criteria of methodology and material manipulation process, as well as the recognized architectural quality these projects have achieved. It thus intends to critically understand the advantages that this technology can bring to architecture, questioning the paradigm of mass production and strengthening the uprising concept of Mass-Customization.